The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1745506520953348
|View full text |Cite
|
Sign up to set email alerts
|

We get double slammed!”: Healthcare experiences of perceived discrimination among low-income African-American women

Abstract: Background: On account of their racial/ethnic minority status, class, and gender, African-American women of low socioeconomic status are among the least privileged, underserved, and most marginalized groups in the United States. Generally, African Americans continue to experience poorer health outcomes, in which disparities have been attributed to socioeconomic inequities and structural racism. This objective of this study was to explore the lived experiences of low-income African-American women in interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 61 publications
2
21
0
1
Order By: Relevance
“…The type of communication patients receive during clinical encounters is associated with their overall health care experience. Studies have observed lower quality communication during health care visits among racial and ethnic minority patients than among white patients [34][35][36] and alarming racial biases in assessing and treating pain. 37 A growing body of literature [38][39][40][41][42][43] posits that addressing this issue is all the more important during the perinatal period, therefore, improving patient-provider relationships by way of tackling perceived discrimination and problematic communication encounters is a needed strategy to reduce racial disparities in maternity care and birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The type of communication patients receive during clinical encounters is associated with their overall health care experience. Studies have observed lower quality communication during health care visits among racial and ethnic minority patients than among white patients [34][35][36] and alarming racial biases in assessing and treating pain. 37 A growing body of literature [38][39][40][41][42][43] posits that addressing this issue is all the more important during the perinatal period, therefore, improving patient-provider relationships by way of tackling perceived discrimination and problematic communication encounters is a needed strategy to reduce racial disparities in maternity care and birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, low-income, individuals have repeatedly recounted experiences of discrimination based on socioeconomic and racial status during interactions with healthcare providers. 20 These experiences may result in avoidance of healthcare settings and paradoxically increase ED utilisation or avoidable hospitalisations due to inadequate management of chronic illnesses. 21 Persistent health inequities among Medicaid-insured individuals demand focused innovations that are centred in equity principles and bridge coordination and continuity between acute and community health providers.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The impact of marginalising conditions is heightened during the period of transition from hospital to home when individuals are required to obtain medications or durable medical equipment, schedule and access follow-up appointments and understand and execute treatment orders all while coping with competing economic needs 19. In addition, low-income, individuals have repeatedly recounted experiences of discrimination based on socioeconomic and racial status during interactions with healthcare providers 20. These experiences may result in avoidance of healthcare settings and paradoxically increase ED utilisation or avoidable hospitalisations due to inadequate management of chronic illnesses 21…”
Section: Introductionmentioning
confidence: 99%
“…Esto se evidencia en los hallazgos de este estudio, que pese a tener un tamaño de efecto pequeño pero significativo, indica que la PS podría asociarse con obesidad abdominal mediante una secuencia de relaciones que considera variables tales como la discriminación percibida, afectividad negativa y calidad de la dieta. Este resultado es consistente con estudios previos que advierten que personas con menor PS están mayormente expuestas a experiencias de discriminación (Okoro et al, 2020), las cuales generan mayores niveles de estrés (Urzúa et al, 2021) y síntomas depresivos (Qin et al, 2020), lo que a su vez, genera mayor consumo de comida chatarra (Agurs-Collins & Fuemmeler, 2011), influyendo finalmente en el aumento del perímetro de cintura (Mozaffarian, 2016). Pese a lo anterior, es importante considerar que este hallazgo no es conclusivo y debe ser investigado en otros estudios.…”
Section: Discusión Y Conclusionesunclassified